Use of intravenous alprostadil in patients with severe critical ischemia of the lower limbs. (June 2019) - Machado-Alba, Jorge Enrique; Machado-Duque, Manuel E
Objectives: To determine the indications for the use, potential benefits, and adverse reactions of alprostadil in a group of Colombian patients. Methods: A retrospective cross-sectional study was conducted in patients diagnosed with critical limb ischemia who received alprostadil in five hospitals in Colombia between September 2011 and July 2017. We reviewed the clinical records of each patient to obtain the sociodemographic and pharmacological variables, clinical stages, complications, comorbidities, reported effectiveness and adverse reactions. Results: Sixty-one patients treated with alprostadil were evaluated; 50.8% of patients were men, and the average age of 72.5 ± 10.7 years. A total of 86.9% of patients were hypertensive, and 65.6% were diabetic. A total of 77.0% presented ulceration, and this condition was considered as a diabetic foot in 57.4% of patients. A total of 81.9% of patients were classified as Fontaine stage 4; 60.7% received therapy as initially indicated, with an average of 19 days of alprostadil use. Regarding the therapy results, 58.0% of the patients with ulcers or trophic lesions showed improvement, 86.2% showed improvement of pain, and the limb was saved in 72.1% of patients. Conclusions: Critical limb ischemia was presented by patients with advanced age and high cardiovascular risk who were treated during severe and advanced stages where therapeutic options are limited. Treatment with alprostadil achieved satisfactory results with improvement in ulcers, pain, and limb salvage rates in this series of patients.